Psychometric Adequacy of Recovery Enhancing Environment (REE) Measure: CHIME Framework as a Theory Base for a Recovery Measure - Penas, Patricia; Uriarte, Jose Juan; Gorbeña, Susana; Moreno-Calvete, Maria Concepcion; Ridgway, Priscilla; Iraurgi, Ioseba (Frontiers in Psychiatry, 2020)
Purpose The aim of this study was to assess to what extent the recovery elements of the Recovery Enhancing Environment (REE) instrument measured the dimensions proposed by the CHIME framework, (Connectedness, Hope and optimism about future, Identity, Meaning in life and Empowerment dimensions), so as to evaluate personal recovery in people with severe mental illness. Methods Two processes were conducted. Firstly, five experts matched the elements of recovery evaluated by the REE items with the CHIME domains and subdomains. Then, the resulting structure from those experts agreement was analyzed with different confirmatory factor analyses (CFA) using responses to the recovery elements dimension of the REE of 312 mental health service users. Results The percentage of agreements and the kappa coefficients were adequate taking into account the CHIME dimensions (κ = 0.57 to 0.69, total κ = 0.74); however, lower agreement was found at the subdimensions level. Some indexes of the CFA were acceptable for a second order factor analysis [χ2(242)= 346.03, p < 0.001, CFI= 0.931, RMSEA= 0.037 (0.028 to 0.046)] and the most adequate solution was obtained from the bi-factorial structure (χ2(223)=233.19, p=0.306, CFI= 0.993, RMSEA= 0.012 [0.000 to 0.027]). Conclusions Despite the subjective and complex nature of the personal recovery construct, the REE measure can be a valid instrument to verify the existing CHIME conceptual framework, since two of the models tested have resulted in adequate indexes and were also congruent with the theoretical framework and the statistical solution. Thus, REE can be used to obtain a global index of Personal Recovery dimension, and the five indicators proposed by the CHIME framework.